(untitled) (Singaporean Journal of Business Economics and Management, 2014)
The aim of the present study was conducted to the descriptive method; cultural and artistic goods consumption barriers survey. Taking cultural goods cannot be attributed to a single factor, while several factors such as economic, social, media and etc. the cultural consumption is impressive. The results of this study showed that factors such as the existing advertising practices regarding cultural goods, low use of technology in advertising, being inadequate participation of mass communications in the field of informational, cultural goods, prices substandard quality cultural goods distribution network, reducing production subsidies assigned to cultural goods, the role of cultural goods and on family consumption down. Including the most important obstacles facing cultural and artistic consumption.